Extensões de Ore e Álgebras de Weyl - Eugenio, Pedro Alfredo (2013)
In this work we will study the definitions, examples and basic properties of Ore extensions. In particular, we will present a special case of Ore extensions, the Weyl algebras An(K) over a field K. We will see that An(K) is a simple noetherian domain. We will study also the dimension d(M) of a finitely generated An(K)-module and we will prove the Bernstein's inequality, n d(M) 2n. Finally we will study the holonomic An(K)- modules, that is, the finitely generated An(K)-modules such that d(M) = n: